Les services de Santé Sexuelle et Reproductive en Tunisie. Résultats d’une recherche qualitative auprès des jeunes usagers - Atf Gherissi; Francine Tinsa (L’Année du Maghreb)
This study aims to analyze the perceptions of sexual and reproductive health (SRH) services made available to young girls and boys and to identify the determinants of their satisfaction. The conceptual framework is based on the theoretical models of Donabedian (1980, 1982, 1988), Bruce (1990) and Ware (1983). A content analysis was carried out on the basis of group-centered interviews with 42 young people from three urban, rural and suburb environments. The data collection and analysis respected the integrity of the respondents (World Medical Association, 2008) such as anonymity, confidentiality, freedom to participate in the group interviews and to answer the questions in the preferred language. Discussions revealed a deliberate amalgam between knowledge, perceptions and use of RH services. This attitude seems to be sought by all the young people who, throughout the interviews and regardless the place of residence, have obviously often evoked their own experience by projecting their comments on young people in general and in an impersonal way. The results of this study provide relevant information for the future development of SRH services and structures so that they can become their effective users through adapting the national plan and strengthening its implementation. In addition, this study needs to be updated to explore the potential effects of the Arab Spring on youth SRH perceptions and behaviors.